2013
DOI: 10.1128/aac.02226-12
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and Dose-Response Relationships of Liposomal Amphotericin B against Different Azole-Resistant Aspergillus fumigatus Isolates in a Murine Model of Disseminated Aspergillosis

Abstract: bThe management of invasive aspergillosis (IA) has become more complicated due to the emergence of acquired azole resistance in Aspergillus fumigatus, which is associated with treatment failure and a mortality rate of 88%. Treatment with liposomal amphotericin B (L-AmB) may be a useful alternative to improve therapeutic outcome in azole-resistant IA. Four clinical A. fumigatus isolates obtained from patients with proven IA were studied in a nonneutropenic murine model of infection: a wildtype isolate without m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
(68 reference statements)
0
27
0
1
Order By: Relevance
“…Voriconazole is recommended for IPA due to A. fumigatus if the isolate is voriconazole-susceptible (susceptible if MIC ≤1 mg/L) whilst in the case of resistance (MIC >2 mg/L) LAmB therapy is preferred. Where the voriconazole MIC equals 2 mg/L (intermediate) the response to voriconazole monotherapy is unknown [58]. A growing problem in IPA treatment is the intrinsic resistance to polyenes and azoles or the acquired resistance to azoles during azole therapy mainly in patients with chronic pulmonary aspergillosis (CPA) [59].…”
Section: Invasive Aspergillosismentioning
confidence: 99%
“…Voriconazole is recommended for IPA due to A. fumigatus if the isolate is voriconazole-susceptible (susceptible if MIC ≤1 mg/L) whilst in the case of resistance (MIC >2 mg/L) LAmB therapy is preferred. Where the voriconazole MIC equals 2 mg/L (intermediate) the response to voriconazole monotherapy is unknown [58]. A growing problem in IPA treatment is the intrinsic resistance to polyenes and azoles or the acquired resistance to azoles during azole therapy mainly in patients with chronic pulmonary aspergillosis (CPA) [59].…”
Section: Invasive Aspergillosismentioning
confidence: 99%
“…We have previously shown that liposomal amphotericin B (L-AmB) (Ambisome) is effective against azole-resistant IA using a nonneutropenic murine model of disseminated infection (31). A dose-response relationship was observed that was independent of the presence of an azole resistance mechanism.…”
mentioning
confidence: 95%
“…We previously investigated the efficacy of L-AmB monotherapy in an immunocompetent murine model of IA. In that study, the ED 50 values were 0.29 mg/kg (95% CI, 0.05 to 1.65 mg/kg) for the WT isolate and 0.59 mg/kg (95% CI, 0.02 to 14.80 mg/kg) for the TR 34 /L98H isolate (31). There were also no significant differences in L-AmB efficacy against the WT and azole-resistant isolates in immunocompetent mice (P value ϭ 0.83).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of amphotericin B and the echinocandins in vitro remained unaffected. Liposomal amphotericin B has shown good efficacy in a nonneutropenic murine model of acute azoleresistant invasive aspergillosis (14).…”
mentioning
confidence: 99%